Synthesis of Literature on Antioxidant Activity and Safety of Seroja (Nelumbo nucifera Gaertn.) Plant Relative to Pharmacological Potential - Kendrick Mahapurisa; Ferina Angelia; William (Pro-Life, 2026)
Nelumbo nucifera Gaertn. (Nelumbonaceae), known as the sacred lotus, is widely distributed across Asia and has long been used as food and traditional medicine, although its utilization in Indonesia remains largely ornamental. Interest in its antioxidant potential and its role as a source of bioactive compounds has increased. This review aims to systematically summarize in vitro and in vivo evidence on the antioxidant activity of N. nucifera, identify key plant parts and active compounds, compare extraction and assay methods, and evaluate preclinical bioactivity and safety. Literature searches in Google Scholar, NCBI, and PubMed using the keywords "Seroja" OR "Nelumbo nucifera" AND "antioxidant" yielded 27 eligible articles. Antioxidant activity is mainly attributed to flavonoids, alkaloids, and phenolic compounds, particularly quercetin and neferine. Flowers and seeds generally show higher in vitro antioxidant capacity, whereas leaves and rhizomes are more frequently studied in vivo. Variations in extraction and assay methods contribute to heterogeneous results. Preclinical data suggest a favorable acute safety profile; however, long-term toxicity data remain limited, and no clinical trials have been conducted. Overall, N. nucifera shows promising antioxidant potential, but further standardized toxicological studies and clinical trials are needed to support its therapeutic use.